SECONDARY METABOLITE FROM ENDOPHYTIC FUNGI Chochlibus lunatus OF THE RHIZOME OF TUNJUK LANGIT (Helmynthostachys zaylanica) - Fitrya Fitrya; Muharni Muharni (Universitas Gadjah Mada, 2013)
Helmynthostachys zaylanica which is locally known as tunjuk langit is included Ophioglosaceae genus. The rhizome of tunjuk langit is traditionally used as anticancer. Chochlibolus lunatus was isolated from the tissues of tunjuk langit rhizome. Fungal strain was identified based on the characteristics of its colony and cell morphology. Chochlibolus lunatus was cultured in Potato Dextrose Broth (PDB) medium and it was then extracted using ethylacetate (EtOAc). A secondary metabolite compound was isolated from EtOAc extract. This isolation was done by chromatography technique and the structure of this compound was determined by mean of UV, IR and NMR spectroscopic technique. Isolated compound is like oil. Based on spectra analyses, we concluded that this isolated compound was 11,12,13-trimethylheksyl-2-methylhexa-2,4-dienoat.